Sustainable valorisation of agri-food waste from open-air markets in Kampala, Uganda via standalone and integrated waste conversion technologies. (May 2023) - Somorin, T.; Campos, L.C.; Kinobe, J.R.; Kulabako, R.N.; Afolabi, O.O.D.
Abstract: Though the magnitude of organic-rich agri-food waste arisings from open-air agri-food markets in many sub-Saharan Africa cities such as Kampala, Uganda are largely unknown, the predominant approaches to managing them, i.e., open burning and unsanitary landfilling, are unsustainable, emitting greenhouse gases, and represent an inefficient use of their intrinsic compositional and energy value. This study combined waste-to-energy (WtE) process modelling/simulation, material flow analysis and life cycle assessment to comparatively evaluate the bioenergy production, value-added material recycling opportunities and associated environmental impacts of characterised agri-food waste from three major open-air agri-food markets in Kampala City under three agri-food waste management scenarios: conventional landfilling, standalone (anaerobic digestion, AD) and integrated (hydrothermal carbonisation, HTC & anaerobic digestion; i.e., HTC-AD) technologies. Results reveal that an estimated 14.1 kt (eq. 34.8 TJ) of agri-food waste aggregated from the focus open-air markets is disposed of in an unsanitary landfill annually. Intrinsic agri-food waste compositional analyses evidence suitability for technology-based valorisation scenarios. Further, integrated HTC-AD performed better than standalone AD, marked by higher diversion of input agri-food waste from landfill (91% vs 75% for AD), recovery of diversified fuels (hydrochar and biogas) with higher energy efficiency (ηeff  = 69% vs 45% for AD) and minimal environmental impacts. When benchmarked against landfilling, both technology-based valorisation scenarios significantly reduce (∼96%) adverse environmental responses for most life cycle analysis impact assessment categories. These findings demonstrate the feasibility of addressing the interlinked challenges of agri-food waste management and associated environmental pollution whilst promoting energy/value-added resource recovery from open-air agri-food markets. This is critical and timely to support near-term decision-making on selecting appropriate decentralised WtE technology-based agri-food waste valorisation systems that can realise economic, environmental, and technical (operational and strategic) goals in the city and other similar contexts. Highlights: Open-air markets are strategic hotspots for agri-food waste generation. 34.8 TJ agri-food waste energy-eq. from focus markets are landfilled per year. Managing agri-food waste via HTC-AD improves energy efficiency over AD by 24%. Over half of initial agri-food waste & heavy metals conc. are diverted from landfill. Technology-based valorisations can reduce adverse environmental responses by ≥ 96%.